75.0k views
5 votes
Multiply 3xyz ^ 2 / 6y ^ 4 by 2y / x z ^ 4

2 Answers

3 votes


(3xyz^2)/(6y^4)=(3)/(6)\cdot(xyz^2)/(y^4)=(1)/(2)\cdot(xz)/(y^3)=(xz)/(2y^3)\\\\\\(3xyz^2)/(6y^4)\cdot(2y)/(xz^4)=(xz^2)/(2y^3)\cdot(2y)/(xz^4)=(2)/(2)\cdot(xyz^2)/(xy^3z^4)=1\cdot(1)/(y^2z^2)=(1)/(y^2z^2)

User Dan Hunex
by
5.3k points
3 votes

Answer:

The product of the expression is:


(1)/(y^2z^2)

Explanation:

We are asked to multiply the expression:


(3xyz^2)/(6y^4)* (2y)/(xz^4)

i.e.

The numerator terms get multiplied to each other and the denominator terms get multiplied to each other

i.e. we may write the expression as follows:


=((3xyz^2)\cdot (2y))/((6y^4)\cdot (xz^4))\\\\\\=(6xy^2z^2)/(6xy^4z^4)\\\\=(6)/(6)* (x)/(x)* (y^2)/(y^4)* (z^2)/(z^4)\\\\=y^(2-4)* z^(2-4)\\\\=y^(-2)* z^(-2)\\\\i.e.\\\\=(1)/(y^2)* (1)/(z^2)\\\\=(1)/(y^2z^2)

User Mir Stephen
by
5.7k points